G165(P) Palpitations – a cause for concern?. (27th April 2016) - Stredder, OC; Fisher, J; Damda, F
Abstract : Introduction: Palpitations in children is a common presentation to the Emergency Department. Although usually benign and related to anxiety and stress, it is important to rule out the possibility of cardiac arrhythmia. Palpitations cause significant distress for child and parents. Appropriate initial management and onward referral can ensure accurate diagnosis and minimise the need for unnecessary further investigations whilst reducing anxiety in the family. Methods: A retrospective analysis of ED notes was undertaken. All children under 16 coded for a discharge diagnosis of arrhythmia or palpitations between October 2013 and October 2015 were included. Areas analysed included presentation, adequacy of history taking, physical examination, performance of an ECG and blood tests, advice prior to discharge and onward referral. Results: 84 patients were discharged from ED with a diagnosis of palpitations or arrhythmia. 15 did not meet inclusion criteria. Of the 69 patients analysed, 59% were not asked for family history of cardiac disease, 30% were not asked duration of their symptoms and 58% were not asked about possible triggers. ECG was performed in all but one case. Approximately half of new presentations had blood tests requested. Examination was adequately performed in in almost all patients but pulses were documented in only half of patients.. Appropriate advice was documented for half of the cases. Onward referral was made to the local cardiology clinic in 29% of patients, referral back to GP in 23% and 10% were in existing follow up at specialist tertiary clinics. Conclusions: Nearly 15% of patients presenting with palpitations had arrhythmia, commonly SVT. There was huge disparity in the management of palpitations in our ED. ECGs were routinely performed and most patients had an adequate examination. However, all patients should be asked about family history of cardiac disease, triggers for and duration of palpitations. Examination of pulses should be documented and appropriate advice given at discharge. Where clinically indicated, children presenting with palpitations should have FBC and TFTs. Children with recurrent palpitations will benefit from cardiology outpatient review. We plan to create a protocol for assessment of palpitations in the ED to streamline management.